Deep Crustal Structure Beneath the Pamir–Tibetan Plateau: Insights From the Moho Depth and Vp/Vs Ratio Variation - Murodov, Davlatkhudzha; Mi, Wang; Murodov, Amirkhamza; Oimuhmmadzoda, Ilhomjon; Abdulov, Sherzod; Xin, Wang (Frontiers in Earth Science, 2022)
The Cenozoic convergence between India and Asia has created Earth’s thickest crust in the Pamir–Tibetan plateau, leading to broadly distributed deformation and extensive crustal shortening; however, the crustal deformation of the high plateau is still poorly constrained. The variation of the Moho topography and crustal composition beneath the Pamir–Tibetan plateau has an important correlation with the major tectonic units. In this study, the results of the receiver functions have been reviewed and analyzed to observe variations in the Moho depth and crustal Vp/Vs ratio beneath the Pamir–Tibetan plateau. We found a notable SE–NW-oriented deep Moho interface that starts from the southeast of the Tibetan plateau and continues to the eastern Pamir with a northward dipping direction, which may indicate the northern frontier of the decoupled lower crust of northward underthrusting of the Indian plate. In contrast, the deepest Moho beneath the Pamir plateau has a southward dipping direction indicating the southward underthrusting Asian plate. In general, the average crustal Vp/Vs ratio is relatively low beneath the South-Central Pamir (∼1.70), while it is relatively higher (∼1.75) under the Himalaya–Lhasa terrane, suggesting more felsic to intermediate rock composition with locally high values indicating a low-velocity zone, possibly caused by partial melting. Elevated Vp/Vs ratios are observed beneath the northern Pamir (>1.77) and Qiangtang and Songpan–Ganze terranes (>1.80), which can be related to the high mafic rock content and upwelling hot materials from the upper mantle. The Vp/Vs ratio beneath the Pamir–Tibetan plateau presents complex north–south variations with a relatively low crustal Vp/Vs ratio in the south, while it gradually increases toward the north of the Pamir and central-northern Tibet, which is probably caused by the joint effects of the northward underthrusting Indian lower crust and southward subduction of the Asian plate, the low-velocity zones within the mid-upper crust, and substantial crustal shortening and thickening. The low to average crustal Vp/Vs ratio throughout the plateau (except the central Tibet) indicates a limited amount of hot materials to support the low crustal channel flow model, instead suggesting that crustal thickening and shortening is the main uplifting mechanism of the Pamir–Tibetan plateau.